2003
DOI: 10.1056/nejmoa035071
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-Eluting Stents versus Standard Stents in Patients with Stenosis in a Native Coronary Artery

Abstract: In this randomized clinical trial involving patients with complex coronary lesions, the use of a sirolimus-eluting stent had a consistent treatment effect, reducing the rates of restenosis and associated clinical events in all subgroups analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

65
2,301
18
115

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,898 publications
(2,521 citation statements)
references
References 36 publications
65
2,301
18
115
Order By: Relevance
“…1,2 The introduction of drugeluting stents (DES) has greatly alleviated this problem, 3 and their use in coronary intervention has markedly increased. DES decreases angiographic and clinical measurements of restenosis compared with bare metal stents 4,5 in elective patients and those with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The introduction of drugeluting stents (DES) has greatly alleviated this problem, 3 and their use in coronary intervention has markedly increased. DES decreases angiographic and clinical measurements of restenosis compared with bare metal stents 4,5 in elective patients and those with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently, several randomized and controlled trials have demonstrated great advantages of drug-eluting stents (DESs) in significantly reducing restenosis and recurrence of symptoms, and improving clinical outcomes after percutaneous coronary intervention (PCI). 7,8 Little is known about the comparative effects of 1-DES plus the kissing balloon technique with the 2-DES for bifurcation angioplasty in a Chinese population. Therefore, we conducted the present study to evaluate the immediate and 7-mo follow-up results of PCI for coronary bifurcation lesions treated with implantation of 1-or 2-DES.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, in-stent restenosis for patients treated with either PTA or bare metal stenting continues to be a problem with 3-year primary patency rates below 25% [1]. Drug-eluting stents have markedly reduced restenosis in the coronary vasculature compared to bare metal stents [2,3]. However, drugeluting stents are more expensive and the risk of stent thrombosis mandates longer-term dual antiplatelet therapy.…”
Section: Introductionmentioning
confidence: 99%